Pentingnya SMK3 Pada Sebuah Perusahaan Sebagai Upaya Mencegah Kecelakaan Kerja - Yughni Aulia Nabila; Susilawati Susilawati (Institut Nalanda, 2024)
Occupational Safety and Health (K3) is a crucial aspect in the industrial world which aims to protect workers from the risk of accidents and work-related diseases. Implementing an Occupational Safety and Health Management System (SMK3) in a company is very important as an effort to prevent work accidents. This research aims to analyze the importance of SMK3 in preventing work accidents through literature study methods. This literature study collects data from various sources, including scientific journals, books and research reports related to the implementation of SMK3 in companies. The research results show that implementing SMK3 can effectively reduce the number of work accidents, increase productivity and create a safer work environment. In addition, this research found that management commitment, employee training, and routine monitoring and evaluation are key factors in the successful implementation of SMK3. In this way, companies that integrate SMK3 in their operations not only fulfill legal requirements, but also gain long-term benefits in the form of increased safety and work efficiency.